2019
DOI: 10.4049/jimmunol.1900787
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Role of an IL-23/γδT17/Neutrophil Axis in Coxsackievirus B3–Induced Pancreatitis

Abstract: Coxsackievirus B is a common cause of viral myocarditis and pancreatitis. IL-17A is intensively involved in the pathogenesis of viral myocarditis. Whether IL-17A plays a role in Coxsackievirus B-induced pancreatitis, characterized by acinar cell destruction and immune infiltration, remains largely unknown. We found a significant, but transient, increase of IL-17A expression and gdT influx in the pancreas of C57BL/6J mice within 3 d following CVB3 infection. The pancreatic IL-17A was mainly produced by Vg4 gd T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 67 publications
(66 reference statements)
2
16
0
Order By: Relevance
“…Neutralization with anti‐IL‐17 monoclonal antibody suppressed viral replication and improved cardiac pathology, which suggests that IL‐17 could be a potential target for controlling CVB3 induced AVMC (Yuan et al, 2010 ). Another study on C57BL/6 J mouse model demonstrated the pathogenic role of IL‐17A in CVB3 mediated pancreatitis (Yan et al, 2019 ). In CVB3 patients, the virus induces differentiation of CD4 + T cells into Th17 cells by nucleoporin (Nup) 98 (Long et al, 2016 ).…”
Section: Role Of Il‐17 In Different Viral Infectionsmentioning
confidence: 99%
“…Neutralization with anti‐IL‐17 monoclonal antibody suppressed viral replication and improved cardiac pathology, which suggests that IL‐17 could be a potential target for controlling CVB3 induced AVMC (Yuan et al, 2010 ). Another study on C57BL/6 J mouse model demonstrated the pathogenic role of IL‐17A in CVB3 mediated pancreatitis (Yan et al, 2019 ). In CVB3 patients, the virus induces differentiation of CD4 + T cells into Th17 cells by nucleoporin (Nup) 98 (Long et al, 2016 ).…”
Section: Role Of Il‐17 In Different Viral Infectionsmentioning
confidence: 99%
“…γδT17 cells, in particular Vγ4 + , were critical for viral clearance and protecting mice by recruiting both neutrophils and NK cells, most likely through a CXCL1-dependent mechanism [76]. In contrast to flu, Vγ4-expressing γδT17 cells were shown to be pathogenic during coxsackievirus B virus by inducing acute pancreatitis via their production of IL-17 [77]. Similarly, γδT17 cells also had a pathogenic role in a hepatitis B viral infection model, whereby they induced recruitment of suppressive polymorphonuclear (PMN) cells, leading to CD8 + T-cell exhaustion [78].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Yang demonstrated that IL-17 is increased in the early phase of SAP, confirming that the adaptor protein Card9 coordinates IL-17 to balance immune reactions in SAP pathogenesis ( 75 ). By activating the IL-23/IL-17/neutrophil axis, IL-17A exacerbates virus-induced AP ( 76 ). Thus, the combination of biomarkers will help clinicians develop and adjust the clinical treatment of AP.…”
Section: The Role Of Il-17 In Apmentioning
confidence: 99%